Navigating Allyship through Indigenization, Decolonization, and Reconciliation: Perspectives from Non-Indigenous Pharmacy Educators - Larry Leung; Jason Min (University of Minnesota Libraries Publishing, 2020)
As pharmacy schools across Canada and North America work towards authentic and meaningful curriculum and learning opportunities in Indigenous health and cultural safety, the conversation of "why" we need to do this has become clearer, but the task of "how" we do this remains challenging. This curricular transformation can be increasingly more complex to navigate as a non-Indigenous ally and pharmacy educator. Defining your role as an ally is deeply personal and critically important, as it can transform based on the collaborative work undertaken with Indigenous partners and communities. The purpose of this article is to share perspectives gained over years of experience and practical applications of allyship through the lens of three key separate, but interconnected concepts - indigenization, decolonization, and reconciliation.